A third species of Parakermania Vandel, 1973 (Isopoda: Oniscidea: Armadillidae) from China - Hong, Xinkai; Wang, Yutao; Li, Weichun (Zootaxa, 2022)
Parakermania longa sp. nov., the third species of the woodlouse genus Parakermania Vandel, 1973 is described and illustrated from China. The new species differs from the other two congeners in having a different number of dorsal tubercles, and two well-developed ornamentations on the outer sides of the sixth pereonite going beyond the apex of telson. A key to Parakermania species is provided.